Adolescent hypertension: a growing public health concern in western Maharashtra - Ghuge, Anjali S.; Kadam, Yugantara R.; Kakade, Satish V.; Khurana, Ankur G. (International Journal Of Community Medicine And Public Health, 2026)
Background: As change in lifestyle and food habits in recent years, increased prevalence of high blood pressure among adolescents is observed. Multiple studies have demonstrated that elevated blood pressure in childhood often persist into adulthood. Therefore, early screening is essential to identify adolescents at increased risk of developing hypertension later in life. The study was conducted with objective to estimate proportion of high blood pressure and to identify factors influencing blood pressure. Methods: A cross-sectional analytical study was conducted among 254 adolescents from 5th to 10th grade at secondary schools at Malakapur, Karad, using systematic sampling technique. Data collection was done using a structured questionnaire, a digital sphygmomanometer, an inelastic tape to measure height, an elastic tape to measure waist circumference and weighing machine. Data entry was performed by using Microsoft Excel for Microsoft 365 for windows. Descriptive statistics (percentage/proportion) and Analytical statistics (chi square test) were applied using SPSS Version 27.0. Results: Among 254 adolescents aged 10-17 years, 13% had elevated blood pressure, 7.1% had stage 1 hypertension (HTN), and 5.9% had stage 2 hypertension. Hypertension was significantly more common among male adolescents (17.9% elevated BP and 16.9% HTN) compared with females (9.2% elevated BP and 9.8% HTN) (p=0.017). Overweight and obese adolescents had a significantly higher proportion of HTN compared with those with normal BMI (p<0.001). Conclusions: School based evaluation offers a practical platform to detect influencing lifestyle and behavioral factors. Early identification enables targeted health education and preventive interventions.